Unpacking the emergence of born global founders: A careers perspective. (2nd November 2022) - Pidduck, Robert J.; Shaffer, Margaret A.; Zhang, Yejun; Clark, Daniel R.
ABSTRACT: New ventures that internationalize aggressively from or near founding have been of continued interest in international entrepreneurship. A rich literature now exists in which researchers make numerous distinctions between types or subcategories of rapidly internationalizing firms and how these relate to nuances in performance outcomes. Conversely, little progress has been made toward a theoretical understanding of why these seemingly unique firms emerge in the first place. We contend that a key question remains unanswered: Why do some entrepreneurs from the outset compound the liability of newness, inherent in entrepreneurship, with the liability of foreignness, inherent in internationalization? Drawing from social cognitive careers theory, we developed a model explaining the emergence of entrepreneurial intentions to found explicitly global ventures. We tested our model across two distinct studies, using a multiwave multicountry approach, and found consistent support for an interest pathway to these entrepreneurial intentions. The simple, yet novel, implication is that noneconomic logic shaping entrepreneurs' vocational choices can help explain why some founders take additional risks by overtly focusing on aggressive global growth from inception.